Sex-specific associations between brominated flame retardants exposure and phenotypic age acceleration in NHANES 2005–2010 - Kong, Weiliang; Xie, Yilian; Jin, Yina (Frontiers in Public Health, 2025)
BackgroundExposure to brominated flame retardants (BFRs) has been linked to age-related diseases. This study investigates the associations between both individual and combined BFRs exposures and phenotypic age acceleration (PhenoAgeAccel) in U.S. adults.MethodsData from 3,908 U.S. adults from NHANES 2005–2010 were analyzed. Generalized linear regression models (GLMs) assessed the associations between individual BFRs and PhenoAgeAccel, while weighted quantile sum (WQS) regression and Bayesian Kernel Machine Regression (BKMR) analyses were used to evaluate the effects of combined BFRs exposures.ResultsGLMs indicated significant positive associations between several BFRs and PhenoAgeAccel, including PBDE28 (β = 0.55, 95% CI: 0.13, 0.96), PBDE85 (β = 0.42, 95% CI: 0.11, 0.74), PBDE47 (β = 0.39, 95% CI: 0.04, 0.75), PBDE99 (β = 0.38, 95% CI: 0.07, 0.68), and PBDE154 (β = 0.37, 95% CI: 0.04, 0.70). RCS analysis confirmed nonlinear dose–response relationships for PBDE47 and PBDE99 (P for nonlinearity = 0.03361 and 0.0233, respectively). Stratified analyses revealed that males were more susceptible to BFRs exposure effects, particularly for PBDE99 (P for interaction = 0.027) and PBDE209 (P for interaction = 0.005). The WQS regression showed a significant association between combined BFRs exposure and increased PhenoAgeAccel (β = 0.504, 95% CI: 0.071, 0.937), with PBB153 and PBDE153 as key contributors. BKMR analysis indicated a trend of increasing PhenoAgeAccel with higher BFR exposure levels, primarily driven by PBDE99.ConclusionThis study highlights the significant positive associations between individual and combined BFR exposures and PhenoAgeAccel, with males potentially being more vulnerable to these effects.